2004
DOI: 10.1209/epl/i2003-10185-0
|View full text |Cite
|
Sign up to set email alerts
|

Beam fanning used to study thermal disorder and decay of polar structures in the ferroelectric relaxor Sr 0.61 Ba 0.39 Nb 2 O 6

Abstract: A new photorefractive approach using the temperature evolution of beam fanning to study the polar structure of the ferroelectric relaxor strontium-barium-niobate (SBN) undergoing the ferroelectric-paraelectric phase transition is proposed. A strong temperature dispersion of the decay of polar structures of different sizes is observed. We compare our results with those obtained by other measurement methods to show their dependence on the size distribution of the polar structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…This conclusion was obtained from numerical simulations of the scattering intensity profile, because a linear dependence on the crystal thickness was assumed for the bulk scattering; in contrast to an exponential one for the surface scattering. Recently, it was shown that the scattering in SBN:Ce is strongly dependent on the polar structure of the crystal [24,25]. In particular, the coherent noise (initial scattering) exhibits drastic changes in the vicinity of the phase transition and at the presence of an external electric field E o having a magnitude of the electric coercive field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion was obtained from numerical simulations of the scattering intensity profile, because a linear dependence on the crystal thickness was assumed for the bulk scattering; in contrast to an exponential one for the surface scattering. Recently, it was shown that the scattering in SBN:Ce is strongly dependent on the polar structure of the crystal [24,25]. In particular, the coherent noise (initial scattering) exhibits drastic changes in the vicinity of the phase transition and at the presence of an external electric field E o having a magnitude of the electric coercive field.…”
Section: Resultsmentioning
confidence: 99%
“…The results allowed us to derive a model for the scattering centers in SBN. It was concluded that scattering centers are related to refractive index singularities induced at domain walls by internal electric fields [24,25]. Remarkably, such scattering centers must be located in the crystal bulk or at least within the near-surface region of the crystal-and not on its surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Intensity and angular distribution of the seed scattering is also defined by the spatial order of the ferroelectric domains in SBN. According to the model of seed scattering, 17 period ⌳ results in seed scattering propagating at the angle s = 2 arcsin͑ /2⌳͒. Seed scattering propagating at small s corresponds to large domains, while large-angle scattering is due to small domains.…”
Section: Ferroelectricity Driven Properties Of Parametric Scatteringmentioning
confidence: 99%
“…Therefore, eliminating or at least suppressing the effect of holographic scattering becomes a main goal in order to promote photorefractive crystals for industrial applications [1]. On the other hand, holographic scattering has been advantageously utilized for a wide variety of applications such as optical limiters [2,3], color or coherent--to-incoherent converters [4,5], novelty filters [6,7], vibration object monitoring [8], logic operations [9,10], hologram multiplexing techniques that use random wave generated by beam fanning instead of external diffusers [11] and material characterization [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%